Effect of Training Program on Emotional Intelligence of Nurses Caring for Patients with Alzheimer’s Disease - Bahaa Ali; Omayma Osman; Ghada Mourad (Evidence-Based Nursing Research)
Context: Nurses are the cornerstone of the health care systems, and their work is associated with great pressure, and nurses are often overwhelmed. Emotional intelligence and its significance to nursing have been increasingly emphasized throughout the last few years. Emotional intelligence comprises a deposit of interrelated skills involving a capability to appraise one's emotions and those of others, utilization and regulation of one's emotions, and social skills.